Atriadops Wandolleck, 1897 (Diptera: Nemestrinidae) recorded for the first time from Ecuador - Mengual, Ximo; Hauser, Martin (Zootaxa, 2025)
The genus Atriadops Wandolleck, 1897 (Diptera: Nemestrinidae) occurs in the Neotropical, Afrotropical, Indomalayan and Australasian Regions. It is easily recognized by not having ocelli and the vestigial mouthparts. Out of the seven recognized species worldwide, only one is present in the Neotropics, A. macula (Wiedemann, 1824). We report the first record of Atriadops from Ecuador, a female of A. macula, from the Napo Province, provide the first DNA barcode for the species, and discuss the possible reasons for the low number of records of this genus.